From Books to Bytes: Exploring Social Media Opportunities in the University Libraries - Khan, Muhammad Tufail; Muhammad Rafiq,; Midrar Ullah, (IJoLIS, 2025)
Purpose: This study aimed to explore Social Media Opportunities (SMO) in the University Libraries (UL) of Pakistan. Moreover, differences in respondents' opinions from public and private sector universities, users and non-users of social media, and respondents’ geographical locations were also identified. Methodology: A quantitative research design was employed and data were collected through an online structured questionnaire. The questionnaire was distributed among all head/chief Librarians of 181 universities recognized by the Higher Education Commission (HEC) of Pakistan. However, 124 (69%) valid responses were received out of 181 distributed questionnaires. Findings: The study findings revealed that 54% of university libraries were using social media for library services and showed positive perceptions towards the opportunities offered by social media. Surprisingly, the librarians currently not using social media services showed more positive perceptions than social media users in university libraries. Also, the study revealed that no policy for social media use in university libraries is available. Practical Implications: The findings have theoretical implications for researchers and practical implications for university library administrators, policymakers, and higher education commission decision-makers. Also, help librarians in designing more library services through social media. Originality: This study is among the first attempts to explore the perceptions of university librarians toward social media opportunities for university libraries in an organizational context by covering the whole population.